The effects of tawfik on ethical decision making process: the case of micro and small businesses in Malaysia - Mhd. Sarif, Suhaimi (Journal of Education and Social Science (JESOC), 2016)
This paper examines the effects of tawfik or the will and ability to carry out something in ethical decision making process. Decision making requires art and science in the process to understand issues or problems, consequences of the decisions to the relevant stakeholders, methodology to execute the decisions, and evaluation on the decisions. The study interviewed 10 owners and decision makers of micro and small businesses in Malaysia to solicit their views pertaining to the effects on the will and ability (tawfik) in their decision making process. The informants were personally interviewed with note taking approach within 20-30 minutes duration at their business locations. Most of the informants stated that they used impromptu and rational approach in decision making process just to solve issues or problems at hand without taking into long term consequences of the decisions. The nature of small business requires them to make swift, quick and short term basis decision due to the intense pressure of competition. Sometimes they decided for 'short cut' instead of the long-winded and difficult actions. Some informants argued that sometimes they performed special prayers and making supplications for clueless and too difficult issues, problems and cases. As Muslims, they performed and steadfast with obligatory prayers and other recommended deeds. The informants realized the importance of obtaining tawfik from Allah not only in critical situations but also in all situations. The results of the study are very contextualized and contributed to the insights and understanding of the effects of tawfik in ethical decision making process within the context of selected micro and small businesses in Malaysia. The immediate implication to the theory is in the ethical decision making theory from the Islamic perspectives. In terms of practical implications, the findings of the study can be used as input for micro and small businesses to formulate guidelines in decision making process. The study recommends the future study should expand the number of informants and also to employ triangulation, a combination of interview, survey, and case study.